Controllable Band-Notched Slot Antenna for UWB Communication Systems - Weerathep Kueathaweekun; Noppin Anantrasirichai; Chawalit Benjangkaprasert; Jintana Nakasuwan; Toshio Wakabayashi (My University, 2012)
We propose a slot antenna consisting of a rectangular slot on the ground plane, fed by a microstrip line with a rectangular-ring-shaped tuning stub that can be deployed in ultra-wideband (UWB) communication systems to avoid interference with wireless local area network (WLAN) communication. Our antenna can achieve a single band-notched property from the 5 GHz frequency to the 6 GHz frequency owing to a controllable band notch that uses L- and J-shaped parasitic elements. The antenna characteristics can be modified to tune the band-notched property (4 GHz to 5 GHz or 6 GHz to 7 GHz) and the bandwidth of the band notch (1 GHz to 2 GHz). Furthermore, the shifted notch with enhanced width of the band notch from 1 GHz to 1.5 GHz is described in this paper. The UWB slot antenna and L- and J-shaped parasitic elements also provide the band-rejection function for reference in the WiMAX (3.5 GHz) and WLAN (5 GHz to 6 GHz) regions of the spectrum. Experiment results evidence the return loss performance, radiation patterns, and antenna gains at different operational frequencies.
Keywords: Ground plane; Stub (electronics); WiMAX; Wideband; Return loss; Antenna Design and Analysis